Enhancing Students' Learning Ability Through the Picture and Picture Method in Teaching Information and Communication Technology - Lidya Lestari Hutagaol (PT. Mifandi Mandiri Digital, 2023)
This study aims to improve students' learning outcomes in Information and Communication Technology (ICT) through the Picture and Picture learning model. The subjects of this classroom action research were 21 tenth-grade students of SMA Nasrani 3 Medan as recipients of the action, the ICT teacher as the implementer, a peer teacher as the observer, and the school principal as a data source. Data were collected through tests, observation, and documentation. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The results showed that the application of the Picture and Picture model effectively improved students' ICT learning outcomes. This is evidenced by the increase in the average score from 70.88 before the action to 74.80 in the first cycle and 85.37 in the second cycle. In addition, the percentage of students achieving learning mastery increased from 34.28% before the action to 74.80% in the first cycle and 94.28% in the second cycle. The findings indicate that the Picture and Picture model encourages students to think more critically and engage more actively in solving learning problems.